2020
DOI: 10.1101/2020.04.30.20086264
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lockdown exit strategies and risk of a second epidemic peak: a stochastic agent-based model of SARS-CoV-2 epidemic in France

Abstract: Most European countries have responded to the COVID-19 threat by nationwide implementation of barrier measures and lockdown. However, assuming that population immunity will build up through the epidemic, it is likely to rebound once these measures are relaxed, possibly leading to a second or multiple repeated lockdowns. In this report, we present results of epidemiological modelling that has helped inform policy making in France. We used a stochastic agent-based microsimulation model of the COVID-19 epidemic i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Using a simpler SIR model but a more robust statistical framework Roques et al (2020), found an R 0 between 3.1 and 3.3, but also estimated a temporal reproduction number (R t ) after the lock-down of 0.47 (with a 95% CI of 0.45-0.50). Hoertel et al (2020) developed a detailed 3 All rights reserved. No reuse allowed without permission.…”
Section: Covid-19 Epidemic Modellingmentioning
confidence: 99%
“…Using a simpler SIR model but a more robust statistical framework Roques et al (2020), found an R 0 between 3.1 and 3.3, but also estimated a temporal reproduction number (R t ) after the lock-down of 0.47 (with a 95% CI of 0.45-0.50). Hoertel et al (2020) developed a detailed 3 All rights reserved. No reuse allowed without permission.…”
Section: Covid-19 Epidemic Modellingmentioning
confidence: 99%
“…If the quarantined population return to the susceptible state, and under the assumption that the infectiousness and removal rates remain the same, R t can easily increase above 1 and a second wave of infection is probable. The estimate when to lift lockdowns can be improved and is better addressed by using stochastic models which can give interval estimates of when the community is disease-free 9,14,18,24,25 . While we have implemented a stochastic realization of the model to obtain the time to control the situation, this requires time and computational resources.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies must be done and account for varied dynamics. For instance, agent-based models 18 and social network models 14 have also been used to address similar community interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations